Prinsip Prinsip Dalam Hukum Perkawinan Adat Lampung - M.Hafara Fikario; Zainudin Hasan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The customary marriage law of Lampung is an integral part of Indonesia’s customary legal system, reflecting the social, cultural, and moral values of the Lampung people. This article aims to identify and analyze the fundamental principles underlying Lampung’s customary marriage law and to examine their relevance within the context of national legal development. The research employs a normative juridical method with a descriptive qualitative approach, utilizing literature studies and interviews with traditional leaders. The findings indicate that Lampung’s customary marriage law is based on four main principles: (1) the principle of kinship and mutual cooperation, (2) the principle of balance between rights and obligations, (3) the principle of deliberation and consensus, and (4) the principle of respect for lineage and family dignity. These principles not only serve as guidelines for regulating marital relationships but also play a vital social role in maintaining harmony among clans and preserving social order. In the context of modern law, the values embedded in Lampung’s customary marriage law remain relevant and have the potential to be integrated into the national legal system to strengthen a just and locally rooted legal framework.